Medieval Decorated Ironwork in England - Geddes, Jane (Reports of the Research Committee of the Society of Antiquaries of London, 1999)
This monograph traces the development of the designs and techniques used in the production of ironwork in England from roughly AD 1050 to AD 1500. Found mostly on church doors, chests and tombs, in the form of hinges, handles, knockers or grilles the ironwork of this period is a virtually unexplored aspect of medieval art, and has proved to be a rich source of evidence for design and craft skills.